Justice for victims of human trafficking in Gauteng Province, South Africa - Motseki, Morero Moses (Technium Social Sciences Journal, 2022)
Human trafficking is not a new problem in South Africa and statistics have indicated that it is on the increase. The crime of human trafficking is clandestine and complex. Human trafficking is a complex issue that can be considered from different perspectives and its associated legal framework, in very general terms, states will be responsible for their own acts or omissions that breach their obligations under international law, including human rights law. This article explores and attempts to find solutions for victims of human trafficking. This study utilised a phenomenological qualitative framework following semi-structured interviews. The sampling methods adopted for this study were purposive, using snowball sampling, where the authors could identify the samples, one after the other, through references given earlier. It focused on 40 participants from the Directorate for Priority Crime Investigation (DPCI), the South African Police Service (SAPS), the Department of Home Affairs (DHA), the Department of Social Development (DSD) and the Gauteng Provincial Office, from Pretoria, Springs and Kempton Park. The key findings indicated that the challenges are corruption, lack of motivation and commitment to combat human trafficking, lack of limited awareness and information about the human trafficking scourge in South Africa, the findings also indicated a lack of clear strategy and response by stakeholders to successfully investigate, prosecute and incarcerate the perpetrators of human trafficking and the findings further indicated lack of capacity, resources and training to deal with human trafficking. Based on the findings, the author provided, possible recommendations such as; the utilisation of advanced technology and use of intelligence-led policing to strengthen the work of stakeholders, advanced training and better education including improved awareness strategies; and the utilisation of social media as a tool to deal with human trafficking and strengthening of enforcement responses and reporting techniques.